2016
DOI: 10.1192/bjp.bp.114.155689
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between white matter integrity and serum cortisol levels in drug-naive patients with major depressive disorder: Diffusion tensor imaging study using tract-based spatial statistics

Abstract: Our findings indicate that the elevated cortisol levels in the MDD group may injure the white matter integrity in the frontal-subcortical and frontal-limbic circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 45 publications
(65 reference statements)
4
28
0
Order By: Relevance
“…Indeed, previous studies reported that high cortisol levels were associated with specific brain structure abnormalities in MDD, such as in the anterior cingulate cortex (Treadway et al, 2009) and amygdala (Schuhmacher et al, 2012). Additionally, we previously reported that high cortisol levels were linked with medial orbitofrontal cortex thinning (Liu et al, 2015) and white matter tract disconnectivity in frontal-limbic and frontal-subcortical circuits, which are considered to constitute an element in the pathogenesis of MDD (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, previous studies reported that high cortisol levels were associated with specific brain structure abnormalities in MDD, such as in the anterior cingulate cortex (Treadway et al, 2009) and amygdala (Schuhmacher et al, 2012). Additionally, we previously reported that high cortisol levels were linked with medial orbitofrontal cortex thinning (Liu et al, 2015) and white matter tract disconnectivity in frontal-limbic and frontal-subcortical circuits, which are considered to constitute an element in the pathogenesis of MDD (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…Therefore, high cortisol levels may be linked to brain morphology abnormalities in MDD. Additionally, we previously reported that high cortisol levels were linked with medial orbitofrontal cortex thinning (Liu et al, 2015) and white matter tract disconnectivity in frontal-limbic and frontal-subcortical circuits, which are considered to constitute an element in the pathogenesis of MDD (Liu et al, 2016). Additionally, we previously reported that high cortisol levels were linked with medial orbitofrontal cortex thinning (Liu et al, 2015) and white matter tract disconnectivity in frontal-limbic and frontal-subcortical circuits, which are considered to constitute an element in the pathogenesis of MDD (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They evaluated the relationship between WM integrity during a first depressive episode in drug‐naive patients with MDD using TBSS method. Also in this case, the MDD group was found to have significantly reduced FA values in the IFOF, UF and ATR [Liu et al, ]. Zou et al, by using a voxel‐based analysis, investigated the difference in FA in a group of 45 patients with MDD compared with 45 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several past preliminary studies found that alterations of the white matter, both in size and morphology, were associated with a diagnosis of depression (Nobuhara et al, ; Nobuhara et al, ; Taylor et al, ) and depression outcomes (Alexopoulos, Kiosses, Choi, Murphy, & Lim, ; Bae et al, ; Taylor et al, ). In fact, the white matter atrophy reported in patients with depression was accompanied by high white matter hyperintensities (WMH) on magnetic resonance imaging (MRI), which most likely represents white matter fiber dysmyelination (Aizenstein et al, ; Dalby et al, ), as well as by low fractional anisotropy (FA) on diffusion tensor imaging (DTI), which most likely represents decreased integrity of myelinated fibers in the white matter (Liu et al, ; Xiao, He, McWhinnie, & Yao, ). Furthermore, lesions of myelinated fibers in the white matter were positively correlated with the severity of depression (Iosifescu et al, ), and subjects with severe damage to myelinated fibers of the white matter had a poor response to antidepressants (Papakostas et al, ; Tham, Woon, Sum, Lee, & Sim, ), indicating that the myelinated fibers of the white matter may not only participate in the pathomechanism of depression but also play an extremely important role in the mechanism of antidepressant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several past preliminary studies found that alterations of the white matter, both in size and morphology, were associated with a diagnosis of depression (Nobuhara et al, 2004;Nobuhara et al, 2006;Taylor et al, 2004) and depression outcomes (Alexopoulos, Kiosses, Choi, Murphy, & Lim, 2002;Bae et al, 2006;Taylor et al, 2004). In fact, the white matter atrophy reported in patients with depression was accompanied by high white matter hyperintensities (WMH) on magnetic resonance imaging (MRI), which most likely represents white matter fiber dysmyelination (Aizenstein et al, 2011;Dalby et al, 2010), as well as by low fractional anisotropy (FA) on diffusion tensor imaging (DTI), which most likely represents decreased integrity of myelinated fibers in the white matter (Liu et al, 2016;Xiao, He, McWhinnie, & Yao, 2015).…”
mentioning
confidence: 99%